New atrial arrhythmia occurrence in single chamber implantable cardioverter defibrillator patients: A real‐world investigation. (30th December 2022) - Patel, Divyang; Rao, Archana; Friedman, Paul A.; Deshmukh, Abhishek J.; Lande, Jeff; Murphy, Jeffrey A.; Brown, Mark L.; Lexcen, Daniel R.; Wilkoff, Bruce L.
Abstract: Introduction: A current limitation of single chamber implantable cardioverter defibrillators (ICDs) is the lack of an atrial lead to reliably detect atrial fibrillation (AF) episodes. A novel ventricular based atrial fibrillation (VBAF) detection algorithm was created for single chamber ICDs to assess R‐R variability for detection of AF. Methods: Patients implanted with Visia AF™ ICDs were prospectively enrolled in the Medtronic Product Surveillance Registry from December 15, 2015 to January 23, 2019 and followed with at least 30 days of monitoring with the algorithm. Time to device‐detected daily burden of AF ≥ 6 min, ≥6 h, and ≥23 h were reported. Clinical actions after device‐detected AF were recorded. Results: A total of 291 patients were enrolled with a mean follow‐up of 22.5 ± 7.9 months. Of these, 212 (73%) had no prior history of AF at device implant. However, 38% of these individuals had AF detected with the VBAF algorithm with daily burden of ≥6 min within two years of implant. In these 80 patients with newly detected AF by their ICD, 23 (29%) had a confirmed clinical diagnosis of AF by their provider. Of patients with a clinical diagnosis of AF, nine (39%) were newly placed on anticoagulation, including five of five (100%) patients having a burden >23 h. Conclusions: Continuous AF monitoring with the new VBAF algorithm permits early identification and actionable treatment for patients with undiagnosed AF that may improve patient outcomes.